Access to and use of Tobacco Production Health Hazard Information Sources by Tobacco Farmers in Kuria West Sub – County, Migori County, Kenya - Jackson Manchare Chacha; Hellen Amunga; Raymond Ongus (Journal of Information and Knowledge, 2022)
Tobacco production poses serious dangers to tobacco farmers especially in developing countries. Previous studies have shown that tobacco production activities continue to expose tobacco farmers to health risk. This study examines sources of health hazard information that tobacco farmers in Kuria West Sub- County of Migori County, Kenya access and use in an effort to protect themselves. The data was collected from a sample size of 100 tobacco farmers and 41 key informants. A representative sample was chosen from the four selected wards of Kuria West Sub-County. Software Packages for Social Sciences (SPSS) was used to analyse data. A major finding was that majority of tobacco farmers used various sources of information whose adequacy about potential risks associated with the crop farming remained a challenge. The paper concludes that, the sources of information that tobacco farmers relied on are unreliable and not trustworthy. The study recommends the establishment of Non- partisan organisations to train and disseminate relevant information on health hazards to tobacco farmers.